Respuesta :
Answer:
The resulting equation is
x^2/4+16x^2/9=1
Step-by-step explanation:
The given equations are:
3y=12x eq(1)
x^2/4+y^2/9=1 eq(2)
We need to isolate variable y in equation 1
Divide both sides of the equation with 3
3y/3 = 12x/3
y = 4x
Now, substitute the value of y=4x in second equation
x^2/4+y^2/9=1
x^2/4 + (4x)^2/9 = 1
The resulting equation is
x^2/4+16x^2/9=1
Answer:
[tex]\frac{x^2}{4}+\frac{(4x)^2}{9}=1[/tex]
Step-by-step explanation:
Given system of equations,
[tex]3y=12x-----(1)[/tex]
[tex]\frac{x^2}{4}+\frac{y^2}{9}=1----(2)[/tex]
As per statement,
Isolating the variable y in the first equation,
[tex]y=\frac{12}{3}x=4[/tex]
Now, substituting into the second equation,
[tex]\frac{x^2}{4}+\frac{(4x)^2}{9}=1[/tex]
Which is the resulting equation,
Simplifying the equation,
[tex]\frac{x^2}{4}+\frac{16x^2}{9}=1[/tex]
[tex]\frac{9x^2+64x^2}{36}=1[/tex]
[tex]73x^2=36[/tex]